Rheological Investigation of Lipid Polymer Hybrid Nanocarriers for Oral Delivery of Felodipine (Conference Paper )# - Drais, Hayder Kadhim; Hussein, Ahmed Abbas (Iraqi Journal of Pharmaceutical Sciences, 2022)
The rheological behavior among factors that are present in Stokes law can be used to control the stability of the colloidal dispersion system. The felodipine lipid polymer hybrid nanocarriers (LPHNs) is an interesting colloidal dispersion system that is used for rheological characteristic analysis. The LPHNs compose of polymeric components and lipids. This research aims to prepare oral felodipine LPHNs to investigate the effect of independent variables on the rheological behavior of the nanosystem. The microwave-based technique was used to prepare felodipine LPHNs (H1-H9) successfully. All the formulations enter the characterization process for particle size and PDI to ascertain the colloidal properties of the prepared nanosystem then use coaxial rotational digital rheometer for rheological evaluation. The outcomes show that all felodipine LPHNs formulations (H1-H9) had a nanosize and homogenous structure that ascertain colloidal features of the nanodispersion system. The rheogram chart indicates that all of the felodipine LPHNs formulations (H1-H9) show pseudoplastic flow (non-Newtonian flow) that have shear-thinning property. The microwave-based method prepares felodipine LPHNs formulations (H1-H9) that show excellent physical texture that ascertains its ability as a technique for the preparation of nanoparticles. All of the felodipine LPHNs formulations (H1-H9) show pseudoplastic flow that supports the physical stability of the nanosystem.